Philo of Alexandria: On the Contemplative Life : Introduction, Translation and Commentary - Taylor, Joan E. (Philo of Alexandria Commentary Series, 2021)
"On the Contemplative Life is known for its depiction of a philosophical group of Jewish men and women known as the 'Therapeutae'. Yet the reasons for their depiction have been little understood. In the first commentary on the treatise in English for over 100 years, the social, cultural and political background of the times in which Philo lived are shown to be crucial in understanding Philo's purposes. As Alexandrian Jews were vilified and attacked, Philo went to Rome to present the case for his community, faced with intense opposition. Side-stepping direct confrontation, Philo here cleverly presents the Therapeutae as the pinnacle of excellence, most especially in their communal meal, while ridiculing his accusers in a stinging parody of a festive banquet"--